TestAnaAPP: An interactive R-shiny application for various test analysis methods - Youxiang Jiang; Qing Zeng; Hongbo Wen (SoftwareX)
This paper presents TestAnaAPP, an interactive, user-friendly R package designed for conducting psychometric analyses in social science. It offers a comprehensive suite of psychometric analyses, including factor analysis (FA), classical test theory (CTT), unidimensional and multidimensional item response theory (IRT), continuous response model (CRM), and differential item functioning (DIF) analysis. These methods are commonly employed in data mining of tests and questionnaires. As demonstrated in this paper, TestAnaAPP empowers researchers and practitioners from diverse fields with an interest in applying psychometric methods to seamlessly perform analyses, access comprehensive data analysis results, generate visualizations, obtain detailed analysis reports, and more.